2013
DOI: 10.1002/jsfa.6316
|View full text |Cite
|
Sign up to set email alerts
|

Comparative digestibility of energy and nutrients and fermentability of dietary fiber in eight cereal grains fed to pigs

Abstract: Dehulled oats provide more energy to diets and should be used if the goal is to increase caloric intake. In contrast, sorghum and rye may be more suitable to control diabetes and manage body weight of humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 43 publications
11
30
0
Order By: Relevance
“…These data are consistent with the average values published by NRC [6]. Barley has a greater concentration of fiber and a reduced concentration of starch compared with corn while the digestibility of starch in barley is lower than in wheat and corn [17,18]. The analyzed GE as well as the nutrient profile of HF and LF barley used in the current study were 4,447 and 4,448 kcal GE, 13.98% and 12.96% for CP as well as 2.64% and 2.57% for EE.…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with the average values published by NRC [6]. Barley has a greater concentration of fiber and a reduced concentration of starch compared with corn while the digestibility of starch in barley is lower than in wheat and corn [17,18]. The analyzed GE as well as the nutrient profile of HF and LF barley used in the current study were 4,447 and 4,448 kcal GE, 13.98% and 12.96% for CP as well as 2.64% and 2.57% for EE.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study by Cervantes-Pahm et al (163) reported on the use of a pig model to investigate the comparative nutrient and energy digestibility of a range of grains widely used for human consumption, including wholegrain sorghum. In this study, the apparent ileal digestibility of sorghum starch was lower than for corn.…”
Section: Effects On Glycemic Controlmentioning
confidence: 99%
“…In this study, the apparent ileal digestibility of sorghum starch was lower than for corn. (163) The authors attributed this to the high level of resistant starch in sorghum, which appeared to be fully fermented in the pig hindgut since ~100% starch disappearance was reported. The low apparent ileal digestibility of its starch in pigs suggests that sorghum may be of value for reducing the glycemic index of human foods.…”
Section: Effects On Glycemic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Considered as a prebiotic carbohydrate, low digestibility of RS resulted in decreased apparent ileal and total tract digestibilities of nutrients (Gerrits et al., ; Cervantes‐Pahm et al., ). Hence, a low plasma glucose concentration was observed in pigs fed high‐RS diet (Giuberti et al., ).…”
Section: Introductionmentioning
confidence: 99%